2022
DOI: 10.3390/cancers14215461
|View full text |Cite|
|
Sign up to set email alerts
|

A Risk Model for Patients with PSA-Only Recurrence (Biochemical Recurrence) Based on PSA and PSMA PET/CT: An Individual Patient Data Meta-Analysis

Abstract: An individual patient meta-analysis followed 1216 patients with PSA-only recurrence (biochemical recurrence, BCR) restaged with [68Ga]Ga-PSMA-11 PET/CT before the salvage treatment for median 3.5 years and analyzed the overall survival (OS). A new risk model included a good risk group with a prescan PSA < 0.5 ng/mL (26%), an intermediate risk group with a prescan PSA > 0.5 ng/mL and a PSMA PET/CT with 1 to 5 positive sites (65%), and a poor risk group with a prescan PSA > 0.5 ng/mL and a PSA PET/CT wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…BCR patients were recruited between Dec 2014 and April 2020 at five centers across two continents [ 5 , 7 ]. The University in Ankara, Turkey, reported 94 patients; the Hacettepe University, Ankara, Turkey, reported 102; the University Hospital in Innsbruck, Austria, reported 500; the Johannes Gutenberg University in Mainz, Germany, reported 225; and Sorbonne University, Paris, France, reported 294 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCR patients were recruited between Dec 2014 and April 2020 at five centers across two continents [ 5 , 7 ]. The University in Ankara, Turkey, reported 94 patients; the Hacettepe University, Ankara, Turkey, reported 102; the University Hospital in Innsbruck, Austria, reported 500; the Johannes Gutenberg University in Mainz, Germany, reported 225; and Sorbonne University, Paris, France, reported 294 patients.…”
Section: Methodsmentioning
confidence: 99%
“…A multicenter study of 1216 BCR patients showed that the PSA threshold had a significant impact on their overall survival (OS) [ 5 ]. The European Association of Urology (EAU) published a BCR risk classification [ 6 ], and later, the multicenter study made a new BCR risk model that was based on the pretest PSA threshold and groups by number of positive sites on a restaging PSMA PET/CT [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figure 6. The lower line that shows the control group treatment is ADT + SDaRT + MDT; however, it should only include ADT + MDT.…”
Section: Error In Figurementioning
confidence: 99%